Living mindfully across the lifespan : an intergenerational guide - Penberthy, J. Kim; Penberthy, J. Morgan (New York : Routledge, 2021)
"Living Mindfully Across the Lifespan: An Intergenerational Guide provides user-friendly, empirically-supported information about and answers to some of the most frequently encountered questions and dilemmas of human living, interactions, and emotions. With a mix of empirical data, humor, and personal insight, each chapter engages the reader on a significant topic or question, including self-worth, anxiety, depression, relationships, personal development, loss, and death. Along with exercises that clients and therapists can use in daily practice, chapters feature personal stories and case studies, interwoven throughout with the authors' unique intergenerational perspectives. Compassionate, engaging writing is balanced with a straightforward presentation of research data and practical strategies to help address issues via psychological, behavioral, contemplative, and movement-oriented exercises. Readers will learn how to look deeply at themselves and society, and to apply what has been learned over decades of research and clinical experience to enrich their lives and the lives of others"--
Chapter 1: You Have Worth Just for Existing -- J. Kim Penberthy & J. Morgan Penberthy Chapter 2: Life is Not Fair: Cope with It! -- J. Kim Penberthy & J. Morgan Penberthy Chapter 3: Belief is Half the Battle! -- J. Kim Penberthy & J. Morgan Penberthy Chapter 4: Bringing Others to the Table -- J. Kim Penberthy & J. Morgan Penberthy Chapter 5: Put it in Neutral: Interpersonal Mindfulness -- J. Kim Penberthy & J. Morgan Penberthy Chapter 6: Getting to the Goal -- J. Kim Penberthy & J. Morgan Penberthy Chapter 7: All Problems Have Solutions -- J. Kim Penberthy & J. Morgan Penberthy Chapter 8: Life is Hard -- Deal with It! -- J. Kim Penberthy & J. Morgan Penberthy Chapter 9: I Don't Want to Feel This Way! -- J. Kim Penberthy & J. Morgan Penberthy Chapter 10: Feeling Crappy? Coping with Pain -- J. Kim Penberthy & J. Morgan Penberthy Chapter 11: Feeling Happy? Maintaining Joy -- J. Kim Penberthy & J. Morgan Penberthy Chapter 12: So Long for Now? -- J. Kim Penberthy & J. Morgan Penberthy Epilogue
OCLC-licensed vendor bibliographic record.
Keywords: Cognitive therapy; Behavior therapy; Therapist and patient; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health